Children of No Man's Land - Stern, G. B. (Gladys Bronwyn), 1890-1973 (Salt Lake City, UT : Project Gutenberg, 2024)
"Children of No Man$1 (Bs Land" by G. B. Stern is a novel written in the early 20th century, first published in 1919. It explores themes of youth, identity, and cultural tensions against the backdrop of the early years of World War I. The book introduces us to the Marcus family, particularly focusing on siblings Deborah and Richard as they navigate their experiences in a small, stifling German town, Dorzheim, while grappling with personal conflicts and societal expectations. The opening of the novel presents a vivid tableau of familial dynamics, highlighting the contrasting views of freedom and responsibility between the characters, particularly between the older generation, represented by Hermann Marcus, and the younger ones, Ferdinand and Stella. As Deborah prepares to visit her young German friend Lothar, Richard shows disdain for being uprooted from their holiday in Switzerland. The narrative reveals Richard's internal struggles with national identity as they confront the realities of their heritage amid growing tensions due to the war. Scenes of lively debates about literature between the boys further emphasize the differences in cultural upbringing and perspectives, setting the stage for the central themes of the novel surrounding generational conflict, cultural identity, and the impending societal changes brought on by the war. (This is an automatically generated summary.)s
Also published under title: Debatable ground.
Release date is 2024-08-14
MWS and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: World War, 1914-1918 -- England -- Fiction; English fiction -- 20th century